Oral and transdermal delivery of branched amphiphilic peptide capsules in vivo - Nutsch, Kayla E. (Kansas State University, 2020)
Nanocarriers have become a popular platform for delivering nucleic acid for therapeutic and pest control methods. The peptide-based nanocarriers, branched amphiphilic peptide capsules (BAPCs), have shown the ability to deliver plasmid DNA in vitro and in vivo. The mode of administration for nucleic acid, affects the efficiency of delivery and is dependent on the target tissue and environment advantages. Delivering dsRNA orally in insects can provide pest control in the field with minimal to no effect on surrounding species. However, this delivery method has proven to be highly variable. BAPCs facilitate the uptake of dsRNA in Tribolium castaneum when administered orally through their diet. The gene transcripts tested, BiP and Armet, are involved in the unfolded protein response (UPR) and successful knockdown results in lethality. Complexes of dsRNA-BAPCs were shown to cross the gut epithelium and enter the hemolymph, and further visualized in the midgut epithelial cells, fat bodies, and Malpighian tubules. Transdermal delivery of nucleic acids and compounds is challenging due to the layers of protective barriers of the skin. Magnetic nanobeads surrounded by a bilayer of branched amphiphilic peptides (BAP-MNBs) were tested for transdermal delivery in mice tails with various skin contact times (1 min, 5 min, 15 min, and 30 min) and post exposure incubation times (1 h, 8 h, and 24 h). BAP-MNBs were extracted from tissues using magnetic separation to look at biodistribution as a pilot study. BAP-MNBs suggest a preference for entering through the follicular pathway and accumulate in the spleen, indicating potential for transdermal delivery of DNA vaccines.
Keywords: Branched Amphiphilic Peptide Capsules; Tribolium castaneum; Oral delivery; Transdermal delivery